Decreasing disparity in cholesterol screening in minority communities—findings from the Racial and Ethnic Approaches to Community Health 2010. Issue 4 (6th August 2009) - Liao, Y; Tucker, P; Siegel, P; Liburd, L; Giles, W H
Abstract : Background: Highly controlled research projects demonstrated success in preventing and controlling cardiovascular diseases. Community-based programs have yet to demonstrate significant influence. Data on large-scale community-level interventions targeting minority communities are limited. The aim of this study is to measure the impact of the Racial and Ethnic Approaches to Community Health (REACH 2010) project, a community-based intervention to eliminate racial/ethnic disparities in blood cholesterol screening in minority communities. Methods: Annual survey data from 2001 to 2006 were gathered in 22 communities. Trends in the prevalence of age-standardised blood cholesterol screening were examined for four racial/ethnic groups (black, Hispanic, Asian and American Indian/Alaska Native), stratified by education level, and compared with national data from the Behavioral Risk Factor Surveillance System. Results: The prevalence of cholesterol screening increased among persons in black, Hispanic and Asian REACH communities (p<0.001), whereas prevalence decreased in the total US and Hispanic populations (p<0.001) and remained similar among blacks and Asians nationwide. The relative disparity between the total US population and most REACH communities decreased (p<0.05). Relative disparity in cholesterol screening related to education level decreased (p<0.05) within REACH communities, whereas relative disparity related to education level nationwide remained similar in blacks and increased (p<0.001) in Hispanics. Conclusion: The REACH project decreased racial and ethnic disparities in cholesterol screening between REACH communities and the total US population, as well as disparities related to education level within REACH communities.